Responsible computing during COVID-19 and beyond - Barocas, Solon; Biega, Asia J.; Boyarskaya, Margarita; Crawford, Kate; Daumé III, Hal; Dudík, Miro; Fish, Benjamin; Gray, Mary L.; Hecht, Brent; Olteanu, Alexandra; Poursabzi, Forough; Stark, Luke; et al. (Communications of the ACM, 2021)
Navigating the ethical and societal impacts of technologies.
https://doi.org/10.1145/3466612